Hemifusion in Synaptic Vesicle Cycle - Kweon, Dae-Hyuk; Kong, Byoungjae; Shin, Yeon-Kyun (Frontiers in Molecular Neuroscience, 2017)
In the neuron, early neurotransmitters are released through the fusion pore prior to the complete vesicle fusion. It has been thought that the fusion pore is a gap junction-like structure made of transmembrane domains of SNARE (soluble N-ethylmaleimide-sensitive-factor attachment protein receptor) proteins. However, evidence has accumulated that lipid mixing occurs prior to the neurotransmitter release through the fusion pore lined predominantly with lipids. To explain these observations, the hemifusion, a membrane structure in which two bilayers are partially merged, has emerged as a key step preceding the formation of the fusion pore. Furthermore, the hemifusion appears to be the bona fide intermediate step not only for the synaptic vesicle cycle, but for a wide range of membrane remodeling processes, such as viral membrane fusion and endocytotic membrane fission.